2022
DOI: 10.1186/s12903-022-02557-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone defect size on the 3D accuracy of alveolar bone augmentation performed with additively manufactured patient-specific titanium mesh

Abstract: Objective Additively manufactured (3D-printed) titanium meshes have been adopted in the dental field as non-resorbable membranes for guided bone regeneration (GBR) surgery. However, according to previous studies, inaccuracies between planned and created bone volume and contour are common, and many reasons have been speculated to affect its accuracy. The size of the alveolar bone defect can significantly increase patient-specific titanium mesh design and surgical difficulty. Therefore, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, a recent systematic review did not find a significant difference in exposure rates between conventional and customized meshes, 125 whereas another review did see this difference 126 . For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5–7 mm vertically and 4–5 mm in horizontal height, or did not give exact data on the augmented volume 121,124,127–131 . In one case series, a vertical and horizontal gain of up to 9 mm with an exposure rate of 1/10 cases was reported 132 .…”
Section: Stabilization Of Particulated Graftsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, a recent systematic review did not find a significant difference in exposure rates between conventional and customized meshes, 125 whereas another review did see this difference 126 . For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5–7 mm vertically and 4–5 mm in horizontal height, or did not give exact data on the augmented volume 121,124,127–131 . In one case series, a vertical and horizontal gain of up to 9 mm with an exposure rate of 1/10 cases was reported 132 .…”
Section: Stabilization Of Particulated Graftsmentioning
confidence: 97%
“…126 For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5-7 mm vertically and 4-5 mm in horizontal height, or did not give exact data on the augmented volume. 121,124,[127][128][129][130][131] In one case series, a vertical and horizontal gain of up to 9 mm with an exposure rate of 1/10 cases was reported. 132 In "large" defects (mean reconstructed bone volume 1004 mm 3 ), Lizio et al 228 summarized a failure rate of 5/19 sites.…”
Section: Titanium Meshesmentioning
confidence: 99%
“…The studies were from four categories: c before-after (Pre-Post) studies with no control g [46][47][48][49][50][51], and case series/case report studies [52-57…”
Section: Risk Of Biasmentioning
confidence: 99%
“…The Cochrane Collaboration tool was applied included in this review (Table 1), using the judgin S4 (Supplementary Materials). A moderate risk of Chiapasco 2021 [49] Prosthesis 2023, 5, FOR PEER REVIEW Table S3 (Supplementary M the reasons for exclusion The studies were from before-after (Pre-Post) studies [46][47][48][49][50][51], and case series/case re…”
Section: Risk Of Biasmentioning
confidence: 99%
“…However, our previous retrospective study showed that although the created bone volume increases roughly as the planned, the final created bone contour differed from the planned contour in the alveolar bone defect reconstruction sites. 14,15 It had been proposed that the placement accuracy of customized mesh, connective tissue layer beneath the customized mesh, gingival cracking, exposure of customized mesh, and other clinical complications affect final created bone recovery and contour. 16 For obvious reason, the surgical placement of customized mesh should be considered as the most fundamental and critical factor.…”
Section: Introductionmentioning
confidence: 99%